2018
DOI: 10.3389/fneur.2018.00603
|View full text |Cite
|
Sign up to set email alerts
|

Communication Matters—Pitfalls and Promise of Hightech Communication Devices in Palliative Care of Severely Physically Disabled Patients With Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is the most common motor neuron disease, leading to progressive paralysis, dysarthria, dysphagia, and respiratory disabilities. Therapy is mostly focused on palliative interventions. During the course of the disease, verbal as well as nonverbal communicative abilities become more and more impaired. In this light, communication has been argued to be “the essence of human life” and crucial for patients' quality of life. High-tech augmentative and alternative communication (HT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 188 publications
0
45
0
1
Order By: Relevance
“…Exposure to unnecessary vulnerability is experienced by some patients when accessing AAC. The value of AAC to carers has been identified in reducing carer burden, facilitating greater rewards and social closeness, and reducing difficulty of providing care for people with ALS using AAC . AAC has a critical role in enabling patient autonomy; however, challenges to accessing AAC are reported and are unacceptable.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Exposure to unnecessary vulnerability is experienced by some patients when accessing AAC. The value of AAC to carers has been identified in reducing carer burden, facilitating greater rewards and social closeness, and reducing difficulty of providing care for people with ALS using AAC . AAC has a critical role in enabling patient autonomy; however, challenges to accessing AAC are reported and are unacceptable.…”
Section: Discussionmentioning
confidence: 93%
“…8,9,13,48 The studies included in this review, as well as the broader litera- The value of AAC to carers has been identified in reducing carer burden, facilitating greater rewards and social closeness, and reducing difficulty of providing care for people with ALS using AAC. 49,50 AAC has a critical role in enabling patient autonomy; however, challenges to accessing AAC are reported and are unacceptable. People with ALS report that residing in a rural location, the logistics of navigating funding support for AAC, and the knowledge base of their health care professionals all impacted AAC access and obtaining a communication device in a timely manner.…”
Section: Amyotrophic Lateral Sclerosis and Assisted Ventilationmentioning
confidence: 99%
“…This study suggests that for the first time a touchscreen system could help to improve performance in individuals with ALS, in addition to the potential for using technologies to improve functionality in this group. It is important to emphasize that a game was used to test performance and that we anticipate transfer to other tasks, but this work needs replicating with other technological devices including communication and socialization systems which have been found to promote self- determination, increase patients’ quality of life and reduce caregiver burden [46]. Providing the best device for an individual to perform practical tasks is extremely important, considering health service resources and the impact on participation in meaningful activities of this condition.…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with the social model of health where one's health is influenced by a wide range of individual, interpersonal, organisational, social, environmental, political and economic factors (Yuill, Crinson, & Duncan, 2010) and the results of other studies on nonpharmacological pain management interventions. The studies by Butow and Sharpe (2013) and Linse, Aust, Joos, and Hermann (2018) revealed that good communication, as well as warm and friendly relationships between healthcare providers and patients, improved health outcomes such as pain management.…”
Section: Discussionmentioning
confidence: 99%